The Importance of TOR Kinase in Plant Development - McCready, Kirsty; Spencer, Victoria; Kim, Minsung (Frontiers in Plant Science, 2020)
TARGET OF RAPAMYCIN (TOR) kinase has been recognised as a key developmental regulator in both plants and animals. Despite their distinct developmental programmes, all eukaryotes studied possess a functional TOR kinase, which integrates environmental and nutrient signals to direct growth and development. This is particularly important in plants, as they are sessile and must sense and respond to external signals to coordinate multicellular growth appropriately. Thus, the investigation of TOR is essential for plant developmental studies in the context of the resources available for growth. Recently, links have been shown between TOR and plant development from embryogenesis through to senescence, however more investigation is crucial to fully elucidate TOR function in each developmental process.